Case Report: First case of low-grade myofibroblastic sarcoma of the vulva during pregnancy - Zhu, San; Luo, Yan; Bian, Ce; Zhang, Yaoyao; Yang, Lingyun (Frontiers in Oncology, 2025)
Low-grade myofibroblastic sarcoma (LGMFS) of the vulva is exceptionally rare, with only two prior cases reported. We present the third documented case globally and the first occurring during pregnancy, highlighting diagnostic and therapeutic challenges in this unique clinical scenario. A 34-year-old woman presented with a recurrent vulvar mass initially misdiagnosed as angiomyofibroblastoma. The lesion reappeared asymptomatically during pregnancy and was conservatively managed with ultrasound surveillance, followed by term cesarean delivery to mitigate perineal trauma risks. Postpartum evaluation revealed a 3.7 cm T2-hyperintense nodule on MRI. Although intraoperative frozen sections suggested benign margins, definitive histopathology and molecular studies (CD34+/SMA+; FISH-negative for COL1A1::PDGFB fusion and MDM2 amplification) confirmed LGMFS. Radical vulvectomy with 2 cm margins achieved disease-free survival at 17 months without adjuvant therapies. This case underscores that LGMFS may recur silently during pregnancy, necessitating rigorous histopathological re-evaluation of prior benign diagnoses. Multidisciplinary coordination enabled safe deferral of definitive surgery until postpartum without compromising outcomes, while radical excision alone proved curative, reflecting the tumor’s indolent biology. Our findings establish the first pragmatic framework for managing vulvar LGMFS in pregnancy, emphasizing tailored surgical planning over routine adjuvant interventions.